The wonderful wizard of oz - Baum, L. Frank; Alvarez, Lorena (Usborne London, 2014)
"This special edition of L. Frank Baum's well-loved classic - complete and unabridged - has stunning illustrations by Lorena Alvarez Gomez. Join Dorothy and her dog, Toto, as they are whirled up in a great cyclone, and find themselves in the magical land of Oz."--Back cover